Political Communication Apprehension in an Era of Activism: A Survey of Thai Undergraduates - Young, David (LEARN Journal: Language Education and Acquisition Research Network, 2023)
With student activism on the rise in Thailand, deep divisions have formed both at home and school. This study places the modern Thai student in context with a review of the Thai national character and a look at repression and demonization of student activists over the past century. 175 first- and second-year undergraduates at a high-ranking university in Thailand were administered the Personal Report of Political Communication Apprehension (PRPCA). Results show that students exhibit a moderate degree of Political Communication Apprehension. Results of this study can aid in determining the extent to which instructors wish to engage students in political classroom discussions.